Modelización de la calidad del agua del estero El Limón, Cantón Quevedo, estación seca, Año 2018 - Toapanta Bastidas, Maria Belen (2018)
The modeling of water quality is intended to provide information on behavior, ecological status and predict the scenarios that may occur in a natural stream. This research was carried out with the objective of modeling the water quality to evaluate the behavior or variability of dissolved oxygen and the biochemical demand of oxygen in the El Limón estuary, for which the following specific requirements were met: (1) determine the characteristics hydromorphological of the estuary, (2) to characterize the water quality of the El Limón estuary, (3) to model the water quality with the Streeter-Phelps model, and, (4) to simulate the water quality with the QUAL2K software. Modeling and calibration were carried out using the mathematical expressions established in the Streeter-Phelps model, the data obtained is used, the field phase, the hydrometric and physicochemical characteristics observed in the months of July to October. The calibration of the model consisted in adjusting the kinetic constants of reaaction (ka), deoxygenation (kd) and total removal of the BOD (kr), using the GLUE (Generalized Probability Uncertainty Estimation) methodology, which combines the manual method (error and Test in order to obtain the possible variations of the kinetic constants, through the Monte Carlo simulations Finally, the performance analysis was carried out, where the statistical error between the values measured in the field with the predicted values for the OD and BOD, we find the Nash-Sutcliffe equations and the coefficient of determination (R2), which registered a good adjustment for OD and BOD In the application of the QUAL2K model, the result of the performance analysis was not so favorable for the BOD due to the lack of information necessary to make an optimal adjustment between the values and those predicted by the model.